Leaf area influence in the rooting of superior Gmelina arborea Roxb. genotypes - Villegas-Espinoza, Juan Pablo (2016)
To determine if the leaf area is necessary to ensure the better development of root cuttings for Gmelina arborea in their rooting tunnels. In the interest of this investigation we used Melina clones 5, 6 and 9 withapical cuttings, which were obtained and placed in embedded tunnels. The treatment consisted in reducing the leaf area (8 cm², 12 cm², 16 cm² and 20 cm²) by measuring the graph paper molds. The evaluationcriteria items were Rooting percentage, final height, final leaf area and total biomass of plants within 3 weeks of rooting variables. There were different measuring methods such as ANOVA, Tukey mean test (a = 0.05) and Pearson correlation coefficient with statistical software InfoStat that were applied based on logistic regression by using the statistical software “R”. Rooting average 75.75% influenced by the diameter and green biomass, reporting 78% correlation was reported, and also treatments of 16 cm² and 20 cm², which showed more conclusive results in variable rooting and plant height percentages. Significant differences between treatments were reported in variable end leaf area and total biomass with 20 cm² treatment presented the highest value for both variables. Clone 5 was the one that presented the best results in the variables leaf area and total biomass. The leaf area of 20 cm² showed good results to improve the quality of the rooting process.